Rumination in Adolescence: the Distinctive Impact of Brooding and Reflection on Psychopathology (2018)
Rumination has a crucial role in the onset, severity and maintenance of depression in adolescent and adult populations. The Ruminative Responses Scale (RRS) is the most widely self-report instrument used to assess individual differences in the tendency to engage in ruminative responses style. This paper aims to test the factor structure of the 10-item RRS and the gender-based measurement invariance, in a community sample of adolescents, using a Confirmatory Factor Analysis. Participants were 542 adolescents (53% females) with a mean age of 14 years old (SD = 1.75) from middle and secondary schools (years of education's mean = 9.46, SD = 1.60) in Portugal. Results confirm the two-factor structure of the RRS composed by brooding and reflection dimensions (GFI = .93, CFI = .90, TLI = .87, SRMR = .05, RMSEA = .11, 90% C.I. [0.092 to 0.121]) and the invariance across gender (GFI = .91, CFI = .89, TLI = .85, RMSEA = .08, 90% C.I. [0.069 to 0.090], p < .001). RRS and their dimensions presented a good internal reliability (Brooding: α = .80; Reflection: α = .75; RRS total: α = .85). Brooding and reflection dimensions revealed moderate correlations with depression, anxiety and stress symptoms (p < .001). Multiple Regression Analysis through Structural Equation Modelling (SEM) showed that brooding is significantly and strongly associated with internalizing symptoms (p < .001). Female adolescents reported more levels of rumination than male adolescents. Overall, these findings support the usefulness of the Portuguese version of RRS and suggest that this short version is an economical, valid and reliable measure to assess ruminative response styles in adolescence.